Pyracantha coccinea roem. (rosaceae) as a biomonitor for cd, pb and zn in mugla province (Turkey) - (:unkn) unknown (My University, 2008)
This study was firstly aimed to find out the measures of Cd, Pb and Zn as the heavy metal pollution in Mugla Province, and secondly if Pyracantha coccinea Roem. (firethorn) can be used as a biomonitor and phytoremediation. P. coccinea samples were collected from 34 localities in four different areas of Mugla Province, during vegetation period in 2006. The Cd, Pb, and Zn concentrations of unwashed and washed leaf samples and unwashed branch samples were measured by ICP-OES. As a result of measurements, the average highest value of Cd accumulation has been reached in unwashed leaf samples, which were collected near highways. The value was 0.36±0.60 μg g-1 dw. The lowest value was detected as 0.16±0.04 μg g-1 dw, in washed leaf samples which were found in industrial area. The average highest value of Pb (14.93±1.23 μg g-1 dw) was determined in the branch samples collected in industrial area whilst the lowest (5.60±1.47 μg g-1 dw) were in washed leaf samples collected in industrial area too. The highest Zn (15.57±1.66 μg g-1 dw) was measured in the branch samples collected in city center, whilst the lowest was measured in the branch samples (8.99±1.32 μg g-1 dw) collected in city center too. It was proven that P. coccinea can be used as a biomonitor species for these heavy metals. It was also observed that this species could be used for phytoremediation procedure.